SISTEM INFORMASI GEOGRAFIS BANTUAN RUMAH LAYAK HUNI BERBASIS WEB PADA DINAS SOSIAL KABUPATEN BOLAANG MONGONDOW UTARA - Marlin Lasena; Dedi Tambayong (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2016)
The aim of the research is to design a Geographic InformationSystem Help Home Livable Web Based On Social Department NorthBolaang Mongondow, the data collection process is expected to improve theeffectiveness and efficiency of information on appropriate housing to thecommunity. The method used in this research is descriptive method, isresearch which seeks to solve the problems that exist now systematicallybased on the existing data in a systematic, factual and accurate informationon the facts, nature and the relationship between the phenomenon understudy. To test this system using white box testing by selecting the modules ofthe web to be converted into a flowchart and then flow graph calculatedafter CC (Cyclometer Complexity) and Black box testing to obtain the testresults are correct. Based on test results, we concluded that theGeographical Information System Web-Based Help Home Livable canimprove the effectiveness and efficiency of the process of providinginformation on appropriate housing to the community.